Methodology standardization for assessing leadership patterns among postgraduate agricultural students - Sangappa; Rafi, D; Laxmi, B; Srinivasa, B K; Tara, S C (Plant Science Today, 2025)
Leadership plays an essential role in developing professional competence, enhancing decision-making ability and fostering effective teamwork in agricultural education. The present study aimed to identify dominant leadership styles and to analyse factors influencing leadership behaviour among postgraduate agriculture students. The present study was conducted among postgraduate students enrolled in state agricultural universities in Southern India during 2024-25 academic year, with a sample size of 200 respondents selected through random sampling techniques. A descriptive-cum-analytical research design was employed to examine their leadership style, locus of control and resilience orientation. Standardized psychometric methodologies were used for primary data collection, including the leadership effectiveness and adaptability description (LEAD) questionnaire, based on the Hersey and Blanchard situational leadership model and the Nicholson McBride resilience questionnaire (NMRQ). The collected data were analysed to understand the adaptability of leadership behaviour and resilience characteristics among agricultural postgraduates. Both descriptive statistics and the multinomial logistic regression model were employed for analysis. Results revealed that the participating leadership style (38.00 %) was most prevalent among agricultural students, followed by delegating (32.50 %), telling (17.00 %) and selling (12.50 %). The model fitting test (χ² = 38.130; df = 21; p = 0.012) indicated that the fitted model was statistically significant at 1 % level. Among the predictors, gender, order of birth and locus of control significantly influenced leadership orientation, while variables such as previous education background, decision-making ability and future goal orientation were not significant. The findings underscore the need to integrate structured leadership training and psychological development programs within agricultural education to enhance adaptive, inclusive and resilient leadership competencies among future professionals.